Proposal of a Knowledge Self-Management Model for the Productivity of Small Companies in the Age of Knowledge [Proposition D Un Modèle D Autogestion Des Connaissances Pour la Productivité Des Petites Entreprises À L Ère Du Savoir] [Proposta de Modelo Para a Autogestão Do Conhecimento Para a Produtividade Das Empresas de Menor Porte Na Era Do Conhecimento] [Propuesta de Modelo Para la Autogestión del Conocimiento Para la Productividad de Las Empresas de Menor Tamaño en la Era del Conocimiento] - Roa-Petrasic, V; Rojas-Pescio, H (Universidad Nacional de Colombia, 2021)
This paper explains the relevance of knowledge as one of the most important intangible assets of organizations, a key element for productivity in the current age of knowledge. In addition, this work establishes the need to manage the explicit knowledge of organizations through the use of information and communication technologies (icts) in all its stages: generation, storage, transfer, and evaluation. Hence, we propose a knowledge self-management model that optimizes results and allows rethinking organizational strategies. Results and conclusions on the application of the proposed design to a Chilean microenterprise in the tertiary level of the icts sector are presented; particularly in regard to the knowledge applied in its business processes and its effect on productivity. A mixed approach and a theoretical framework based on knowledge management literature are used, which involves a longitudinal approach in the design of the model. This work seeks a broader understanding of how micro-businesses could better manage their knowledge assets. © 2021, Universidad Nacional de Colombia. All rights reserved.